Diversity and conservation status of fish in the Nijhum Dweep National Park, Bangladesh - Kishor Kumar Sarker; Moumita Saha Saha; Irin Sultana; Naim Khandakar; Sabiha Islam; Mohammad Abdul Baki; Delip K. Das (Journal of Fisheries, 2021)
Nijhum Dweep National Park lacks a detailed inventory of aquatic fauna including fish. This study reported the diversity and abundance of fish along with their conservation status from the surrounding waters of the national park to fill the knowledge gap. Fish samples were collected randomly from 16 spots of surrounding water of the park between October 2017 and March 2018. There were 47 fish species recorded belonging to 10 orders, 27 families and 44 genera. Odontamblyopus rubicundus was the dominant fish species that comprised 20.24% of the total catch, followed by Rhinomugil corsula (15.54%), Mystus gulio (12.03%) and Eleutheronema tetradactylum (9.92%). One nationally Endangered fish species (Clupisoma garua) and three Vulnerable fish species (Gudusia chapra, Sicamugil cascasia and Wallago attu) were recorded. Fish diversity of the park was rich but exceeding extraction rate, huge disposal of by catch, and presence of exotic omnivorous fish species was disconcerting that require monitoring and further studies.